Fabrication and characterizations of a novel etched-tapered single mode optical fiber ammonia sensors integrating PANI/GNF nanocomposite - Mohammed, Husam Abduldaem; Abdul Rashid, Suraya; Abu Bakar, Muhammad Hafiz; Ahmad Anas, Siti Barirah; Mahdi, Mohd Adzir; Yaacob, Mohd Hanif (Elsevier, 2019)
The present work discusses the ammonia (NH3) sensing behavior of etched-tapered single mode fiber (SMF) sensors coated with polyaniline (PANI)/graphite nanofiber (GNF) nanocomposite at room temperature. SMF was etched with hydrofluoric acid and subsequently tapered in a glass processing workstation. The PANI/GNF ratio in the nanocomposite polymer film is 2:1. The etched–tapered SMF is spray-coated with PANI/GNF nanocomposite. By varying the waist SMF diameter, a comprehensive investigation of the optical response of PANI/GNF nanocomposite-coated SMF and etched–tapered SMF sensors at room temperature is performed. The scanning electron microscopy of PANI/GNF nanocomposites showed a high surface-area sensing layer due to formation of porous structures with 1-2 μm dimension. SMF modification significantly increases the interaction of the evanescent field of light that propagates in the core with the PANI/GNF sensing layer. The integration of modified SMF with the PANI/GNF nanocomposite films yields a highly sensitive optical sensor that can be operated at room temperature (26 °C) in the visible wavelength range. The 50-μm etched and then 15-μm tapered SMF coated with PANI/GNF nanocomposite exhibits response time and sensitivity of 58 s and 300, respectively. Moreover, increased surface area in sensitive regions allows the sensor to detect as low as 0.00142% NH3, which is equal to 14.2 ppm. The etched–tapered SMF sensors coated with PANI/GNF nanocomposite exhibits stronger performance toward NH3 in terms of response time and sensitivity as compared with pristine PANI-coated sensors.